Physiological and biochemical measurements on Pycnogonida from McMurdo Sound ... - Moran, Amy; Tobalske, Bret; Woods, H. Arthur (U.S. Antarctic Program (USAP) Data Center, 2018)
This dataset contains morphometric (mass, surface area, cuticle thickness, cuticle morphometrics) and physiological (oxygen consumption) data for Antarctic pycnognonids collected in McMurdo Sound, Antarctica . ...